Constraints encountered by farm women in vegetable farming in Mandi district of Himachal Pradesh - YADAV, D S; CHAHAL, V P; SINGH, UMMED; KUMAR, ARVIND; SOOD, PANKAJ (The Indian Journal of Agricultural Sciences, 2016)
The study identified constraints encountered by farm women in vegetable farming in Mandi district of Himachal Pradesh. The data were personally collected from 100 farm women of two vegetable growing blocks of the district by using multi-stage sampling technique. Overall, majority (69%) of respondents encountered medium to high extent of constraints. The study revealed that lack of knowledge about enterprise, marketing linkages, schemes of developmental departments, training and financial institutions, lack of financial institutions and difficulty in getting loan, high cost and non-availability of quality inputs in time, lack of entrepreneurship development oriented trainings and requisite support were the major constraints. Lack of marketing centers, low price of produce, lack of storage and irrigation facilities, non-availability of labour, and stray animals were the major general constraints. Effective policy at government level for stray animals and monkeys, timely availability of quality inputs at subsidized rates, promotion of processing units and financial institutes at village level and trainings on entrepreneurship development for socio economic upliftment of farm women are the prime concerns to be looked upon.